Incubator Analyzer Function Test in Laboratory Scale: Temperature Uniformity, Relative Humidity, Noise Level and Airflow - Handayani, Indah Nursyamsi; Mamurotun; Suharyati; Muthmainnah, Syamila Yasmin; Muhammad, Farhan (Universitas Indonesia, 2023)
A function test is conducted to assess the equipment's performance, component function, output, and safety. The aim of the incubator analyzer function test is to determine the performance parameters, including mattress temperature, ambient temperature, humidity, noise, and airflow. In this article, we present an analysis of a prototype incubator analyzer through a comparative test method against a standard incubator analyzer. The testing procedure adheres to SNI IEC 60601-2-19-2014, which outlines special requirements for the basic safety and essential performance of infant incubators. The incubator analyzer prototype was designed using specific components such as PT100 resistive temperature detector, single chip humidity sensor module SHT 11, airflow sensor, microphone amplifier MAX4466 as a sound sensor, and a human-machine interface Nextion display. The function test of the incubator analyzer was conducted at an authorized institution on a laboratory scale. The results indicate that the prototype achieves an accuracy of over 98% for temperature measurement and more than 94% for relative humidity at temperature settings of 32°C and 36 °C.